Lessons from Panama on combining REDD+ and land restoration to reduce net emissions - Rivera, Ovidio; Hyman, Glenn G.; Castaño, Silvia Elena; Espinosa, Herlin; Labatte, Gabriel; Mariscal, Emilio; Montenegro, Ricardo (2016)
Panama, like other tropical countries, is undergoing land-use change that is contributing to greenhouse gas emissions. An analysis was made of the principal land-use changes, losses and gains of carbon stocks and potential impacts on livelihoods. We also analyzed the potential of policies to reduce net emissions through the REDD and Alliance for the Million Hectares (AMH).